2005
DOI: 10.1007/s00421-005-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular lipid and glycogen content are reduced following resistance exercise in untrained healthy males

Abstract: Resistance exercise has recently been shown to improve whole-body insulin sensitivity in healthy males. Whether this is accompanied by an exercise-induced decline in skeletal muscle glycogen and/or lipid content remains to be established. In the present study, we determined fibre-type-specific changes in skeletal muscle substrate content following a single resistance exercise session. After an overnight fast, eight untrained healthy lean males participated in a approximately 45 min resistance exercise session.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 50 publications
6
104
1
Order By: Relevance
“…Sections were stained using laminin (Sigma) and N2.261 (developed by Dr. Helen M. Blau, obtained from the Developmental Studies Hybridoma Bank developed under the auspices of the NICHD and maintained by The University of Iowa, Department of Biology, Iowa City, IA) antibodies to assess the fiber type-specific cross-sectional area and the percentage of myosin IIa isoforms and succinate dehydrogenase (SDH) activity to determine fiber type proportions (37,38). Digital images were obtained using an upright microscope with a camera (Axio Imager D1, Carl Zeiss, Wrek Göttingen, Germany), controlled by AxioVision AC software (AxioVision AC Rel.…”
Section: Methodsmentioning
confidence: 99%
“…Sections were stained using laminin (Sigma) and N2.261 (developed by Dr. Helen M. Blau, obtained from the Developmental Studies Hybridoma Bank developed under the auspices of the NICHD and maintained by The University of Iowa, Department of Biology, Iowa City, IA) antibodies to assess the fiber type-specific cross-sectional area and the percentage of myosin IIa isoforms and succinate dehydrogenase (SDH) activity to determine fiber type proportions (37,38). Digital images were obtained using an upright microscope with a camera (Axio Imager D1, Carl Zeiss, Wrek Göttingen, Germany), controlled by AxioVision AC software (AxioVision AC Rel.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that resistance exercise depletes glycogen stores (105) . Thus, sufficient carbohydrate intake to restore muscle glycogen would be necessary to support high-intensity training.…”
Section: Potential Problems With High-protein Dietsmentioning
confidence: 99%
“…Previous studies have shown that changes in muscle fibre-type composition (20)(21)(22)(23), muscle oxidative capacity (MUOX) (24) and intramyocellular lipid (IMCL) (25,26) and/or glycogen (25) content are associated with the development of skeletal muscle insulin resistance. Although insulin sensitivity has been reported to improve following resistance (27)(28)(29) as well as endurance-type (2, 30-32) exercise training, the concomitant structural changes in resting IMCL and/or glycogen content following exercise interventions in T2D patients remain controversial (33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%